A genetic model for neurorehabilitation - Custódio, Ricardo Duarte (2019)
ABSTRACT: Coordinated walking behavior in vertebrates and multi-legged invertebrates is controlled by evolutionarily conserved neuronal networks capable of generating movement in a fast, stable, and energy-efficient way. At the same time, it provides the flexibility to adapt to changes in the terrain, load, and under extreme conditions, to changes in internal motor representations resulting from adaptation to injury or disease. Our aim is to understand and characterize the neuronal mechanisms of plasticity that mediate motor adaptation to injury. To do so, we use Drosophila melanogaster, an easily manipulatable animal model with a powerful genetic toolkit, and the FlyWalker System that allows quantification of locomotor behavior of freely-walking Drosophila with high spatial and temporal resolution. In order to study motor recovery, we submit flies to a middle-leg amputation and quantify locomotor behavior over the course of time. We found that, although highly uncoordinated, Drosophila melanogaster can walk immediately after amputation. Over time, we observe a gradual improvement in coordination and increasingly controlled gate choice, with several parameters returning to control values. Moreover, we found that this behavior is phenocopied in D. repleta and D. pseudoobscura, two distant Drosophila species, hence showing that the phenotype of locomotor recovery after limb injury is evolutionarily conserved in the Drosophilidae phylogenetic tree. We then tested several classic Learning and Memory mutants pertaining to the cAMP signaling pathway for Long Term Memory (amnesiac, rutabaga, dunce and radish); these mutants displayed little signs of locomotor recovery – reflected in the absence of gait adaptation, inability to stabilize the body during walking bursts and decreased footprint precision and accuracy; over time these add up, resulting in a locomotor behavior phenotype in which the flies are inaccurate and random in each step taken, and hence walk in an increasingly uncoordinated fashion. Additionally, we tested inhibition of de novo protein synthesis using the translation inhibitor Cycloheximide, which yielded no palpable results. These results indicate that flies can readjust their neuronal-motor circuitry to an injured state, observable through a time-dependent recovery in locomotor performance, and that this behavioral phenotype is evolutionarily conserved throughout the Drosophilidae phylogenetic tree. Moreover, general genetically encoded mechanisms relevant for memory and learning (described by classical olfactory learning paradigms) may be involved in this process of locomotor adaptation and recovery – possibly by promoting neuronal plasticity events. By identifying specific genes and their expression patterns in the nervous system occurring during motor adaptation, we will be able to genetically dissect and target mechanisms of neuronal plasticity involved in locomotor recovery.